2010
DOI: 10.1080/03601234.2010.493476
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and sensitive fluoroimmunoassay based on quantum dot for the detection of chlorpyrifos residue in drinking water

Abstract: A rapid and sensitive indirect competitive fluorescence-linked immunosorbent assay (cFLISA) method based on quantum dots as the fluorescence label coupled with secondary antibody (Ab(2)) for the detection of chlorpyrifos in drinking water has been developed. The cFLISA method allowed for chlorpyrifos determination in a liner working range of 15.2-205.5 ng mL(-1). The 50 % inhibition value (IC(50)) and the limit of detection (LOD) of the cFLISA were 50.2 ng mL(-1) and 8.4 ng mL(-1), while the IC(50) and the LOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…There was a permissible occurrence of carbendazim and chlorpyrifos residues in parsley which grown without application of any pesticide. It confirms that the pesticide residues (carbendazim and chlorpyrifos) were transfered by a surface water to soil agricultural of parsley [8,14,36]. Crum et al [37] had found in his study that the highest sorption of nine common pesticides (include chlopyrifos and carbendazim) to aquatic macrophytes (its structure is very similar to parsley) was chlorpyrifos.…”
Section: Sample Analysismentioning
confidence: 52%
See 2 more Smart Citations
“…There was a permissible occurrence of carbendazim and chlorpyrifos residues in parsley which grown without application of any pesticide. It confirms that the pesticide residues (carbendazim and chlorpyrifos) were transfered by a surface water to soil agricultural of parsley [8,14,36]. Crum et al [37] had found in his study that the highest sorption of nine common pesticides (include chlopyrifos and carbendazim) to aquatic macrophytes (its structure is very similar to parsley) was chlorpyrifos.…”
Section: Sample Analysismentioning
confidence: 52%
“…Chlorpyrifos, has been widely employed in agriculture to kill pests which has a wide environmental endocrine disruptor and its residual mainly exists in crops, livestock, poultry products and also led to their migration into aquifers which is potentially hazardous to health [1,2,5,8,15]. Unfortunately, Chlorpyrifos with a thiophosphoryl (P=S) functional group is important causes of morbidity and mortality following intentional self-poisoning or in cases of occupational or environmental exposure [1,5,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this reaction, the carboxyl group on the surface of the quantum dot is first activated by N-Hydroxysuccinimide (NHS), and the activated carboxyl group forms an amide bond with the original amino group on the surface of the antibody under the action of EDC (Ji et al, 2005;Wang et al, 2017;Wu et al, 2019). In addition, there are non-covalent bond binding methods, such as biotin and avidin non-covalent bond coupling, covalent bond bonding and amino group and sulfhydryl covalent bond bonding (Chen et al, 2010;Taton, 2000;Zajac, Song, Qian, & Zhukov, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Management of pests in tea plantations has largely depended on the use of conventional, neuron toxic, broad-spectrum synthetic chemical pesticides [1]. Organophosphorus (OP) and carbamates (CM) compounds are widely used in agriculture because of the efficiency for insect killing, easy synthesis, and low cost [2]. The above pesticide residues are harmful to the environment, human health, and animals through the nervous system poisoning by the way of inhibiting the activity of AChE, the most important enzyme involved in nerve transmission [3].…”
Section: Introductionmentioning
confidence: 99%